Innovative and cost-effective fabrication technique for dielectric composite material - Nurfarhana, Mustafa; Syamimi Mardiah, Shaharum; Kitazawa, Toshihide; Mohamad Shaiful, Abdul Karim (Semarak Ilmu Publishing, 2024)
In this paper, the fabrication process of epoxy resin and nanocomposite barium titanate using cost-effective apparatus is presented along with measurements of complex permittivity. The material is prepared by mixing epoxy resin and barium titanate powder which has high permittivity. Measurement of complex permittivity of materials is performed using a waveguide technique in the G-band with a frequency between 4 and 6 GHz. The results are then compared with the previous works that use advanced and precision instrumentation. The results indicate that the material’s permittivity, determined using our proposed technique, performs admirably. Specifically, at a frequency of 5 GHz, the permittivity is 7.32 with a loss tangent of 0.025 for a filler concentration of 20%. These values not only meet but also closely match those obtained with high-end equipment. Therefore, the proposed technique could be a good potential as an alternative technique for dielectric material preparation which is suitable to be used as a substrate antenna.